Nuclear-cytoplasmic interaction for stigma receptivity in Indian mustard (Brassica juncea) hybrid development - KUMAR, SHAHIL; CHAKRABARTY, S K; SINGH, NAVEEN; KUMAR, ANUJ; C T, MANJUNATH PRASAD; BASU, SUDIPTA (The Indian Journal of Agricultural Sciences, 2023)
Field experiments were conducted during 2020–21 and 2021–22 at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi to study the response of stigma receptivity in 30 new CMS lines, based on 3 new cytoplasmic male sterile (CMS) sources namely, Moricandia, erucoides and berthautii of Indian mustard [Brassica juncea (L.) Czern.] using two traits, i.e. per cent siliquae set and seed set per siliquae which are important for hybrid seed yield in seed production. CMS lines showed varying responses to distinct genetic backgrounds. Per cent siliquae set and seed set per siliquae changed due to cytoplasmic-nuclear interaction. Studies on stigma receptivity evaluation using manual pollination up to 7 days since anthesis revealed that it varies among the 3 CMS sources of Brassica juncea. Peak stigma receptivity reached up to 2 to 3 days following flower opening. Among the 3 CMS sources berthautii showed higher stigma receptivity compared to Moricandia and erucoides. Among the nuclear genotypes, Pusa Tarak was the most promising. The new CMS sources would be useful for hybrid development based on higher stigma receptivity for hybrid seed production. These findings will aid in the selection of appropriate nucleo-cytoplasmic combinations for use in the B. juncea hybrid breeding programmes.